Polymeric Ablative Composite Materials and their Application in the Manufacture of Aerospace Propulsion Components - Robayo-Salazar, Rafael; Portocarrero-Hermann, Julián; Díaz-Padrón, Ubaldo; Patiño-Castrillón, Oscar (Universidad Pedagógica y Tecnológica de Colombia, 2020)
The development of thermal protection systems and high-temperature composite materials for the manufacture of low-weight propulsion components represents a major challenge for the aerospace industry, especially in the field of rocketry. The rocket combustion chamber and nozzles must be designed to withstand operating temperatures above 1600-2000 ° C in a severe ablative environment. This research focuses on obtaining a characterization of ablative composite materials based on a polyester resin matrix (30%) reinforced with particulate materials (fillers) (67%) and short glass fibers (3%), highlighting that the fillers correspond to industrial waste or by-products such as steel slag, aluminum slag, foundry slag and ceramic waste. The composites were physically and mechanically characterized and subjected to an ablative direct flame test (~1600-2000 °C, 120 seconds), reporting thermal insulation levels between 72.6-92.9%, with maximum temperatures on the opposite side of the flame between 141.6-548.8 ° C, and post-ablative weight losses of between 8.5-13.2%. Based on the obtained results, the optimal composites were selected and their application was validated in the manufacture of rocket-type nozzle propulsion components, which were subjected to a real static combustion test, using a solid propellant Candy KNSu type (65 % KNO3-35% Sucrose). The results proved the possibility of obtaining ablative composites and thermal protection systems from available materials and high contents of industrial by-products. These applications are considered important to develop the Colombian aerospace field in the construction of sounding rockets for scientific, technological, and military purposes.